2023
DOI: 10.1136/bmjopen-2022-069001
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of medical students to sexism and sexual harassment and their association with mental health: a cross-sectional study at a Swiss medical school

Abstract: ObjectivesTo assess the self-reported prevalence of sexism and sexual harassment at a Swiss medical school, and to investigate their association with mental health. Research hypotheses were an association between sexism/sexual harassment and poor mental health and a higher prevalence of sexism/sexual harassment in clinical rotations.DesignCross-sectional study as a part of ETMED-L project, an ongoing cohort study of interpersonal competences and mental health of medical students.SettingSingle-centre Swiss stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Further analysis revealed that women, as well as multi-racial students, were at greater odds of being harassed by faculty and staff (McClain et al 2021). One study which examined students from all French faculties, 20% of female participants reported being victims of SH under the definition of French Law (Duba et al 2020), meanwhile another study reported 1 in 4 students experienced harassment (Barbier et al 2023). One particularly large French study reports student faced sexual harassment and aggression during their studies (Rolland et al 2022).…”
Section: Characteristics Of Victims and Victimizersmentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis revealed that women, as well as multi-racial students, were at greater odds of being harassed by faculty and staff (McClain et al 2021). One study which examined students from all French faculties, 20% of female participants reported being victims of SH under the definition of French Law (Duba et al 2020), meanwhile another study reported 1 in 4 students experienced harassment (Barbier et al 2023). One particularly large French study reports student faced sexual harassment and aggression during their studies (Rolland et al 2022).…”
Section: Characteristics Of Victims and Victimizersmentioning
confidence: 99%
“…Meanwhile, females who reported SH experienced significant feelings of burnout (Mahurin et al 2022). Students also reported significant feelings of cynicism and emotional exhaustion (Barbier et al 2023), and guilt and progressive isolation (Babaria et al 2012).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…This substantial body of research shows that both SH and GH are associated with decrements to mental health including increased depression, anxiety, and suicidal ideation [ 8 , 13 , 14 ]. Recent cross-sectional research continues to show associations between SH and greater symptoms of depression, anxiety, suicidality, or poor mental well-being in samples as varied as women soldiers in Belgium [ 15 ], men and women medical school faculty in the Midwestern US [ 16 ], men and women medical students in France [ 17 ] and Switzerland [ 18 ], and international humanitarian field workers [ 19 ]. Research on GH, or closely related constructs such as workplace bullying, is not as common as SH research.…”
Section: Introductionmentioning
confidence: 99%